The house beyond the dunes - Burton, Mary (Mary T.) (Montlake, 2023)
Lane McCord wakes up in a hospital after a near-fatal fall at a rented beach cottage in North Carolina. Her boyfriend, Kyle, wasn't so lucky. Confused and grieving, Lane plans to collect her personal belongings from the cottage and get out, until a winter storm leaves her stranded, but not alone. A concerned neighbor, who claims he heard a violent argument before the accident, has come out of the storm. So has a suspicious detective. How well did she know Kyle?